When crime waves - Sacco, Vincent; Sage eBooks (London : SAGE, 2005)
A critical examination of crime waves aimed at an undergraduate audience. Historical & contemporary examples are drawn primarily from the US, but international examples are threaded throughout for comparison.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Crime; Criminology; Criminal statistics; Mass media and crime; Criminal justice, Administration of; Electronic books